Diversity and prevalence of type VI secretion system effectors in clinical Pseudomonas aeruginosa isolates - Robinson, Luca A.; Collins, Alice C. Z.; Murphy, Ronan A.; Davies, Jane C.; Allsopp, Luke P. (Frontiers in Microbiology, 2023)
Pseudomonas aeruginosa is an opportunistic pathogen and a major driver of morbidity and mortality in people with Cystic Fibrosis (CF). The Type VI secretion system (T6SS) is a molecular nanomachine that translocates effectors across the bacterial membrane into target cells or the extracellular environment enabling intermicrobial interaction. P. aeruginosa encodes three T6SS clusters, the H1-, H2- and H3-T6SS, and numerous orphan islands. Genetic diversity of T6SS-associated effectors in P. aeruginosa has been noted in reference strains but has yet to be explored in clinical isolates. Here, we perform a comprehensive bioinformatic analysis of the pangenome and T6SS effector genes in 52 high-quality clinical P. aeruginosa genomes isolated from CF patients and housed in the Personalised Approach to P. aeruginosa strain repository. We confirm that the clinical CF isolate pangenome is open and principally made up of accessory and unique genes that may provide strain-specific advantages. We observed genetic variability in some effector/immunity encoding genes and show that several well-characterised vgrG and PAAR islands are absent from numerous isolates. Our analysis shows clear evidence of disruption to T6SS genomic loci through transposon, prophage, and mobile genetic element insertions. We identified an orphan vgrG island in P. aeruginosa strain PAK and five clinical isolates using in silico analysis which we denote vgrG7, predicting a gene within this cluster to encode a Tle2 lipase family effector. Close comparison of T6SS loci in clinical isolates compared to reference P. aeruginosa strain PAO1 revealed the presence of genes encoding eight new T6SS effectors with the following putative functions: cytidine deaminase, lipase, metallopeptidase, NADase, and pyocin. Finally, the prevalence of characterised and putative T6SS effectors were assessed in 532 publicly available P. aeruginosa genomes, which suggests the existence of accessory effectors. Our in silico study of the P. aeruginosa T6SS exposes a level of genetic diversity at T6SS genomic loci not seen to date within P. aeruginosa, particularly in CF isolates. As understanding the effector repertoire is key to identifying the targets of T6SSs and its efficacy this comprehensive analysis provides a path for future experimental characterisation of these mediators of intermicrobial competition and host manipulation.